The fourth power : a grand strategy for the United States in the twenty-first century - Hart, Gary, 1936- (Oxford University Press, 2004)
Today, even as it asserts itself globally, America lacks a grand strategy to replace the Cold War's 'containment of communism'. In this volume, Gary Hart, until recently co-chair of the US Commission on National Security in the 21st Century, outlines a new principled approach, based on the power of American ideals, its 'fourth power'.